Knowledge based computational support system to enhance industrial design: conceptual design decision making / Nik Mohamad Farid Nik Ismail - Nik Ismail, Nik Mohamad Farid (Institute of Graduate Studies, UiTM, 2012)
faced by industrial designers in understanding new designs in the process of sketching ideas. In exploring new concepts, industrial designers are required to support their reasoning based on concrete objects and ideas. In doing so, industrial designers normally use sketches to bring forward the ideas and tailor the explanations based on prior knowledge to come up with the new concepts. It is often observed that there is a lack of interactive pedagogical agents that can coach industrial designer“s reasoning and to adapt the explanations to their cognitive state. The design of such agents can be based on learning theories that explains how industrial designers understand new concepts, as well as from studies on how industrial designers support conceptual understanding. Further goal of this research is to develop a computational framework to inform the designers of a pedagogical agent capable of engaging in a drawing dialogue that supports industrial designer“s conceptual understanding.